2022
DOI: 10.1007/s12306-022-00754-x
|View full text |Cite
|
Sign up to set email alerts
|

Freehand power-assisted pedicle screw placement in scoliotic patients: results on 5522 consecutive pedicle screws

Abstract: Pedicle screws is the current gold standard in spine surgery, achieving a solid tricolumnar fixation which is unreachable by wires and hooks. The freehand technique is the most widely adopted for pedicle screws placing. While freehand technique has been classically performed with manual tools, there has been a recent trend toward the use of power tools. However, placing a pedicle screw remains a technically demanding procedure with significant risk of complications. The aim of this article is to retrospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Skaggs et al, in a large multicenter study, reported 99.9% of pedicle screws placed with power pedicle preparation did not have complications or require revision, while 0.5% of screws underwent revision for an asymptomatic lateral breech and for a spinal headache/medial breech [ 24 ]. In the study of the accuracy of screw placement using power [ 51 ], a total of 5522 screws were placed: 96.12% were grade A. The effective accuracy (within the safe zone, grade 1 and 2) was 98.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skaggs et al, in a large multicenter study, reported 99.9% of pedicle screws placed with power pedicle preparation did not have complications or require revision, while 0.5% of screws underwent revision for an asymptomatic lateral breech and for a spinal headache/medial breech [ 24 ]. In the study of the accuracy of screw placement using power [ 51 ], a total of 5522 screws were placed: 96.12% were grade A. The effective accuracy (within the safe zone, grade 1 and 2) was 98.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The effective accuracy (within the safe zone, grade 1 and 2) was 98.6%. No neurological, vascular, or visceral complications were recorded, but four screws needed revision (0.072% of the total) [ 51 ]. The use of robotic-assisted thoracic screw placement was studied by Macke et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the most common fixation technique at our institution was the Luque-Galveston technique with all sublaminar wires (52.0%) or hybrid constructs (46.6%), which included a combination of sublaminar wires, hooks, and/or pedicle screws. Pedicle screw instrumentation is currently the most common instrumentation for posterior spinal fusion due to its ability to achieve stronger segmental fixation and the concept of three-column fixation [6,25]. Thus, our findings may differ from long-term outcomes for present-day patients who receive all-pedicle screw instrumentation.…”
Section: Discussionmentioning
confidence: 63%